2023
DOI: 10.3389/fpsyg.2023.1104057
|View full text |Cite
|
Sign up to set email alerts
|

The influence of stressful life events on procrastination among college students: multiple mediating roles of stress beliefs and core self-evaluations

Abstract: IntroductionFew studies have documented the relationship between stressful life events and procrastination, which is a prevalent and troubling problem among college students. In this regard, the current study examined the association between stressful life events and procrastination through potential mediating effects of stress beliefs and core self-evaluations.MethodsA cross-sectional design was carried out and data were collected from a total of 794 Chinese college students with measures of stressful life ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Although procrastination is not a formal symptom of depression, it is a behavior often experienced by people living with depression [ 46 , 53 , 54 , 55 , 56 ]. Research has shown that procrastination is associated with various mental health challenges, including depression, anxiety, stress, and low self-esteem [ 44 , 45 , 46 , 47 , 48 , 53 , 54 ]. Also, academic procrastination was related to diminished academic performance and depression symptom severity in previous studies [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although procrastination is not a formal symptom of depression, it is a behavior often experienced by people living with depression [ 46 , 53 , 54 , 55 , 56 ]. Research has shown that procrastination is associated with various mental health challenges, including depression, anxiety, stress, and low self-esteem [ 44 , 45 , 46 , 47 , 48 , 53 , 54 ]. Also, academic procrastination was related to diminished academic performance and depression symptom severity in previous studies [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Procrastination is defined as the voluntary delay of an intended action despite the recognition that this delay may have adverse effects, such as compromising performance or increasing stress levels unnecessarily [ 44 , 45 , 46 ]. Procrastination occurs despite an individual having the capability to complete tasks, and it is typically accompanied by a subjective feeling of discomfort, stress, and anxiety [ 47 , 48 ]. Procrastination can manifest in various aspects of life, such as work, academic responsibilities, personal goals, or daily chores [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, life events impose stress levels on patients, activating the hypothalamic-pituitary-adrenal axis and the autonomic nervous system, leading to negative cognitive components such as rumination and maladaptive coping strategies (Heydari Aghdam et al, 2021). Prolonged and frequent confrontation with stress and anxiety from negative life events disrupts mood self-regulation and increases allostatic load in brain areas like the prefrontal cortex and amygdala (Ma et al, 2023;Sabouri & Mansouri, 2022). Therefore, life events lead to psychological distress, a combination of mood problems, depression, and anxiety, which follow maladaptive and self-destructive behaviors that are in opposition to self-care.…”
Section: Discussionmentioning
confidence: 99%